SOCIAL CRITICISM AND LANGUAGE STYLE IN THE POEM “MALU (I) BECOME INDONESIAN PEOPLE” AND “RESTORE INDONESIA TO ME” TAUFIQ ISMAIL’S WORKS - Srastina Srastina; Febriyantina Istiara; Effrina Yuricki (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
The purpose of this study is to describe the style of language and the content of social criticism in the poems “Malu (Aku) Jadi Orang Indonesia” and “Kembalikan Indonesia Padaku” by Taufiq Ismail. The method used in this research is qualitative. The results showed that the poems “Malu (Aku) Jadi Orang Indonesia” and “Kembalikan Indonesia Padaku” by Taufiq Ismail uses six irony styles, three sarcasm styles, four cynicism styles, and eight satire language content. Social criticism of the poem “Malu (Aku) Jadi Orang Indonesia” and “Kembalikan Indonesia Padaku” by Taufiq Ismail, there are social criticisms of moral problems found as many as 13, social criticism of economic problems found as many as four, and social criticism of political problems raised as many as nine.